EXPERIMENTAL DEVELOPMENT AND IMPLEMENTATION OF APPLIED BACCALAUREATE PROGRAM - Baynova, Maria; Paleova, Polina; Evstratova, Tatiana; Sulyagina, Julia; Gorkovaya1, Olga (Revista Inclusiones, 2020)
The article is devoted to modern research in the field of Russian standards of professional education. The experience of conducting educational events is discerned as in the case of the Moscow Banking College of Russian Academy of National Economy and Public Administration under the President of the Russian Federation. In addition, statistics of psychological testing and the results are described. The article contains the main guidelines for extracurricular activity. It considers specifics of professional education in view of the Russian cultural and historical trends as well as scientific progress and modern educational techniques. The pilot project will is used as practically oriented educational standards which meet employers’ requirements.